The Millennial Money Mindset: Redefining Financial Competency - Abdul Rasyid; Andre Prasetya Willim; Siti Khaeryyah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study explores the relationships among Millennial Money Mindset, Economic Environment, Financial Literacy, and Financial Competency at Bank BRI's Pontianak branch. Using a quantitative research design, a sample of 70 customers was randomly selected, and data were analyzed using Smart PLS. The results demonstrate significant direct effects, with Millennial Money Mindset and Economic Environment both positively influencing Financial Literacy and Financial Competency. Additionally, the indirect effects show that Financial Literacy mediates the relationship between Millennial Money Mindset and Financial Competency, as well as between Economic Environment and Financial Competency, indicating that financial literacy plays a crucial role in enhancing financial competency. The findings suggest that fostering a positive millennial mindset and creating a conducive economic environment can improve financial literacy, leading to greater financial competency among customers. For Bank BRI, these results highlight the importance of developing financial education programs, offering tailored digital banking solutions, and engaging with the community to support financial literacy. By adopting these strategies, the bank can better serve its millennial clientele, ultimately contributing to increased customer satisfaction and sustainable business growth.